Rasio Solvabilitas - Intan Alfiyani; Elsya Ainun Nafa Ulfita; Finda Findiana (STEBI Global Mulia Cikarang, 2024)
This research aims to analyze the company’s solvency ratio. Studies on solvency ratios showthat this ratiohas a crucial role in assessing whether a company can pay its long – term costs. The solvency ratio provides insight into the company’s cash flow management and its potential to avoid bankruptcy or face financial challenges. The company's financial statements serve as indicators of future growth and offer a glimpse into its potential for successful performance. Additionally, these statements aid in decision-making processes within the company. Beyond just financial statements, a company’s financial performance is vital, representing its achievements as measured by various ratios that act as benchmarks in financial reports. Evaluating financial performance is essential for companies as it allows for an assessment of their operational effectiveness and efficiency.